2016
DOI: 10.1080/00207233.2016.1165480
|View full text |Cite
|
Sign up to set email alerts
|

Impact and effectiveness of Rwanda’s National Domestic Biogas programme

Abstract: The Rwandan Government's National Domestic Biogas programme (NDBP), seeks to deliver renewable energy services to households across the country by promoting family-sized anaerobic (biogas) digesters on a large scale. The NDBP policy is implemented at different levels, from government and private contractors to households. We analysed the scheme, focusing on how policy was implemented across two districts, namely Kirehe and Kamonyi, and we interviewed rural households and biogas service providers. The NDBP deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Increasing household labour does not encourage uptake of new technologies ( Tucho et al, 2016 ), ( Bansal et al, 2017 ) and may render use of biogas digesters throughout the dry season more unlikely, even for those households in close proximity to water. Such was the case in Rwanda, where it was found women and children preferred to collect firewood than additional water in the dry season ( Kabera et al, 2016 ). Studies from different countries have found that the reduction in the quantity of firewood used by households that use AD is typically 45–60% ( Kelebe and Olorunnisola, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing household labour does not encourage uptake of new technologies ( Tucho et al, 2016 ), ( Bansal et al, 2017 ) and may render use of biogas digesters throughout the dry season more unlikely, even for those households in close proximity to water. Such was the case in Rwanda, where it was found women and children preferred to collect firewood than additional water in the dry season ( Kabera et al, 2016 ). Studies from different countries have found that the reduction in the quantity of firewood used by households that use AD is typically 45–60% ( Kelebe and Olorunnisola, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Feedstock left in the digester without movement since the last wet season could dry out or separate into liquid and solid components, changing the physical, chemical and biological characteristics required for biogas production. In an environment where lack of technical help is widely reported ( Rupf et al, 2015 ; Lwiza et al, 2017 ; Kabera et al, 2016 ), full abandonment of digesters may be an unintended consequence of seasonal dis-adoption as users tend to return to former practices if the technology is not working ( Sime, 2020 ; Barry et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several success stories using cattle dung as feedstock in biogas plants indicate a certain level of technological maturity at the household scale [4,37,41]. Key findings about technical barriers will be found at Table 1 Study of Bhat [43] discovered the lack of storage tanks and pipelines in communal digesters may result in insufficient biogas production, also inadequate design for biogas construction [42] and insufficient feedstock [44]. Studies carried out by Bößner and Silaen et al [20,45] found that biogas output may be insufficient if cow and poultry manure are not always available.…”
Section: Finding 1: Technical Barriersmentioning
confidence: 99%
“…While it is assumed that all institutions will adopt LPG within this time frame, it should be noted that is unlikely that all institutions will use LPG exclusively within this time horizon. In addition, LPG target projections in boarding schools and prisons took into account the existing level of adoption of biogas, which has been promoted in institutions since 2000 [48] as well as for rural household uptake since 2007 [49,50]. It is estimated that only about 40% of the total institutional cooking needs are met through biogas [5], and the remaining 60% was projected to be LPG from 2024 onwards.…”
Section: Overall Lpg Adoption Projections (Residential Institutional ...mentioning
confidence: 99%